Cumulative network-meta-analyses, practice guidelines and actual prescriptions of drug treatments for postmenopausal osteoporosis: a study protocol for cumulative network meta-analyses and meta-epidemiological study. Issue 12 (4th December 2018) - Kataoka, Yuki; Luo, Yan; Chaimani, Anna; Onishi, Akira; Kimachi, Miho; Tsujimoto, Yasushi; Murad, Mohammad Hassan; Li, Tianjing; Cipriani, Andrea; Furukawa, Toshi A
Abstract : Introduction: Cumulative network meta-analysis (NMA) is a method to provide a global comparison of multiple treatments with real-time update to evidence users. Several studies investigated the ranking of cumulative NMA and the recommendations of practice guidelines. However, to the best of our knowledge, no study has evaluated the cumulative NMA ranking and prescription patterns. Here, we present a protocol for a meta-epidemiological investigation to compare the results of cumulative NMA with the recommendations in postmenopausal osteoporosis practice guidelines and with the actual prescriptions. Method and analysis: We will use the data of primary trials from the upcoming postmenopausal osteoporosis clinical practice guideline of the Endocrine Society. We will conduct cumulative NMA using all eligible trials and generate hierarchy of treatment rankings by using the surface under the cumulative ranking curve. We will search practice guidelines in relevant society websites. Two review authors will extract the practice recommendations. We will use data from the Medical Expenditures Panel Survey, a US representative sample of the non-institutionalised population, to determine the prescription patterns. Ethics and dissemination: Because all data will be retrieved from public databases, institutional review board approval is not required. We will publish our findings in a peer-reviewed journal and present key findings at conferences. Trial registration number: UMIN000031894: Pre-results.